An Example of Consistent Spatial and Thematic Data Integration in Large Areas by GIS: the Geological Map of Santa Cruz Province (Argentina) - Asato, Carlos Gabriel (2005)
Fil: Asato, C.G. Servicio Geológico Minero Argentino; Argentina. ORCID: 0000-0002-1968-7741